2022
DOI: 10.1111/jch.14548
|View full text |Cite
|
Sign up to set email alerts
|

The positive correlation between brachial‐ankle pulse wave velocity and aortic diameter in Chinese patients with diabetes

Abstract: Aortic dilation is associated with an increased risk of cardiovascular diseases.Increased brachial-ankle pulse wave velocity (baPWV) is a hallmark of vascular aging and arterial stiffness, as well as an important risk factor for vascular disease. This study aimed to retrospectively analyze the correlation between baPWV and aortic diameter (AoD) of inpatients with diabetes. A total of 1294 diabetic patients with the detailed medical records were investigated. Arterial stiffness was assessed using baPWV and AoD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…PWV is now the gold standard for noninvasive assessment of this process [95]. Several cross-sectional studies have proved a positive correlation between PWV and proximal aortic dilatation in hypertensive patients ( r = 0.247 for carotid–femoral PWV and ascending aorta diameter [89], r = 0.578 for brachial-ankle PWV and aortic root size [11], both P < 0.05). The dilatation of aorta and the increase of PWV may be the different manifestations of the same pathological process in vascular aging and remodeling.…”
Section: Clinical Significance Of Proximal Aorta Dilation In Hyperten...mentioning
confidence: 99%
See 1 more Smart Citation
“…PWV is now the gold standard for noninvasive assessment of this process [95]. Several cross-sectional studies have proved a positive correlation between PWV and proximal aortic dilatation in hypertensive patients ( r = 0.247 for carotid–femoral PWV and ascending aorta diameter [89], r = 0.578 for brachial-ankle PWV and aortic root size [11], both P < 0.05). The dilatation of aorta and the increase of PWV may be the different manifestations of the same pathological process in vascular aging and remodeling.…”
Section: Clinical Significance Of Proximal Aorta Dilation In Hyperten...mentioning
confidence: 99%
“…Additionally, proximal aortic dilatation has been regarded as a morphological manifestation of vascular remodeling and is closely associated with traditional cardiovascular risk factors like left ventricular hypertrophy (LVH) and arteriosclerosis [1,[9][10][11][12]. However, the long-term prognostic value of proximal aortic dilatation has not been confirmed in hypertensive patients, which maybe one of the reasons why this indicator was not included as a risk stratification factor in current guidelines for hypertension [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the association between arterial stiffness and aortic root size, with mixed results. While most studies have found a positive correlation between arterial stiffness and aortic root size [10][11][12][13][14][15], some studies have also reported negative correlations between the two indicators [16]. Notably, all these studies have used non-invasive measures of arterial stiffness, which may have limited accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Research exploring the link between arterial pulsatile hemodynamics and aortic root size has yielded varying results. While the majority of studies indicate a positive correlation between these factors [11][12][13][14][15][16] , there are also reports of negative correlations 17,18 . It is important to note that most of these studies relied on non-invasive methods to gauge arterial pulsatile hemodynamics, which might not be as precise.…”
mentioning
confidence: 99%